2010
DOI: 10.1109/tasc.2010.2041547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quench Propagation in the ITER Poloidal Field Conductor Insert (PFCI)

Abstract: We analyse the issues of quench propagation in the NbTi Poloidal Field Conductor Insert (PFCI), recently tested at JAEA Naka, Japan. The simulation tools Mithrandir, already validated against data from previous Nb3Sn Insert Coils, and M3, implementing a more detailed thermal-hydraulic description of the CICC cross section, are used. The results of the analysis are reported in the paper and compared with experimental data, with particular attention to NbTi versus Nb3Sn features and to the effects of different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…After the first studies in the 1980s [3], the quench experiment on long length was carried out in the mid 1990s on an ITER-like (albeit sub-size) CICC, characterized by the presence of a central cooling channel [4][5][6]. In the first decade of this century, the major role in increasing the database related to this fundamental phenomenon was played by the tests of the ITER insert coils [7][8][9][10][11], which gave rise to a series of computational studies specifically devoted to the topic [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…After the first studies in the 1980s [3], the quench experiment on long length was carried out in the mid 1990s on an ITER-like (albeit sub-size) CICC, characterized by the presence of a central cooling channel [4][5][6]. In the first decade of this century, the major role in increasing the database related to this fundamental phenomenon was played by the tests of the ITER insert coils [7][8][9][10][11], which gave rise to a series of computational studies specifically devoted to the topic [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Another important parameter for the assessment of the conductor performance is the minimum quench energy (MQE). Numerous experimental tests and numerical analyses of this parameter have been performed in the past both on individual strands [18,19] and cable in conduit conductors [20][21][22][23]. Selected results of the MQE tests performed on the Nb-Ti CPQS conductors of the ITER Project are reported here, showing the dependence of the MQE on the temperature margin with respect to the current sharing temperature of each conductor.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the temperature difference between each strand has a dominant impact on the current redistribution compared to the impact of the magnetic field gradient. However, it has been shown that in peculiar cases the magnetic field gradient can have an impact on the quench modeling [67].…”
Section: Resultsmentioning
confidence: 99%